Key drivers for adopting design-build: a comparison study among construction project stakeholders - Z. P., Lee; R. A., Rahman; S. I., Doh (Elsevier Ltd., 2020)
The construction industry in Malaysia recognises the need for a relationship-based procurement by considering the stakeholders to promote the right project delivery method. Design-Build (D-B) is an alternative procurement method that can overcome the incompleteness of Design-Bid-Build (D-B-B) in delivering construction projects. D-B is becoming more common in the United States, China, and Japan, but construction projects in Malaysia are still practising D-B-B. Hence, understanding the drivers of D-B adoption among project stakeholders can determine the root cause for the acceptance or rejection of D-B in Malaysia. This study aims to compare the key drivers for D-B adoption in the Malaysian construction industry among the three main stakeholders, namely client, consultant, and contractor. A questionnaire survey was distributed to 111 professionals with D-B project-related experiences in Malaysia. The results reveal sixteen D-B drivers (DBDs) that affect the stakeholders’ decision in adopting D-B. This study has contributed to the existing literature on D-B by investigating the inter-relationships between DBDs and responses of project stakeholders. The key DBDs can help researchers to formulate strategies to improve D-B adoption for the Malaysian construction industry. The research findings could improve the understanding of DBDs by providing a valuable reference for stakeholders to promote Malaysian D-B.